The Webster's Dictionary of The English Language - Ed. Cayne, Bernard (Lexicon Publications Inc, 1992)
This book aims to combine the best features of the general dictionary and the short entry encyclopedia.
Keywords: Dictionaries-English Language-Reference-Non fiction